THE INFLUENCE OF QUANTUM LEARNING MODELS AND INTERPERSONAL INTELLIGENCE ON STUDENT LEARNING OUTCOMES ON THEME “PERISTIWA DALAM KEHIDUPAN” IN CLASS V SD NEGERI 200301 PADANGSIDIMPUAN - Lia Amalia Harahap; Reh Bungana Br. Perangin-angin; Yusnadi Yusnadi (SENSEI RESEARCH CENTER, 2021)
The research objective is to find out the influence of the Quantum learning model on interpersonal intelligence and the influence of the Quantum learning model on the learning outcomes of students. The research was conducted on fifth grade students at SD Negeri 200301 Padangsidimpuan by taking two classes (experiment class and control class) as many as 50 students. This research was a Quasi Experimental Design type. The data analysis used SPSS 22.0 with a 2x2 factorial. The instruments used were the PPKn learning outcomes test and the Interpersonal Intelligence instrument. Data analysis used two-way ANOVA. The results showed: (1) the influence of the Quantum learning model is higher than the conventional learning model; (2) the learning outcomes of students who have high interpersonal intelligence are higher than students who have low interpersonal intelligence (3) there is the interaction between quantum learning models and students' interpersonal intelligence in influencing student learning outcomes of PPKn. Based on the results of this study, it is suggested that Quantum learning model can be used as an alternative for teacher to improve the ability of interpersonal intelligence and learning outcom of students.